TEACHING READING BY UTILIZING HOT POTATOES SOFTWARE TOWARD STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT - Farih, Abdullah (STKIP PGRI Jombang, 2018)
The objective of this study is to measure whether there is or not significant effect of teaching reading by utilizing Hot Potatoes software toward students’ reading comprehension of descriptive text. The variables used were the teaching treatment of Hot Potatoes Software as the independent variable and the students’ reading comprehension of Descriptive Text as dependent variable. Then, the research designed was Quasi-experimental design and the presentation of data used was quantitative. The data were obtained from the eleventh grade, of which 28 students were taken as sample. The students are divided into two groups; experiment group consisted of 12 students and control group consists of 16 students. To get the data, the pre-test and post-test were applied and then analyzed using t-test formula. The researcher had concluded that there is Significant effect of Hot Potatoes Software toward the students’ reading comprehension achievement. The result showed that mean of students’ post-test was increased. It is proved by the t-test (8.54) which is higher than t-table (2.05) at level of significance 5%. It means that the alternative hypothesis was accepted and it proved that Hot Potatoes Software had significant effect toward students’ reading comprehension of Descriptive Text